Physician‐office vs home uptake of colorectal cancer screening using FOBT/FIT among screening‐eligible US adults. (21st October 2019) - Chido‐Amajuoyi, Onyema Greg; Sharma, Anushree; Talluri, Rajesh; Tami‐Maury, Irene; Shete, Sanjay
Abstract: Background: Guidelines of the American Cancer Society and US Preventive Services Task Force specify that colorectal cancer (CRC) screening using guaiac‐based fecal occult blood test (FOBT)/fecal immunochemical test (FIT) should be done at home. We therefore examined the prevalence and correlates of CRC screening using FOBT/FIT in physicians' office vs at home. Methods: Analysis of 9493 respondents 50‐75 years old from the Cancer Control Supplement of the 2015 National Health Interview Survey was conducted. Weighted multivariable logistic regression was used to identify the determinants of in‐office vs home use of FOBT/FIT for CRC screening. Results: Of the overall sample of screening‐eligible adults (n = 9403), only 937 (10.4%) respondents underwent CRC screening using FOBT/FIT within the past year; among this screening population, 279 (28.3%) respondents were screened in‐office. We found that sociodemographic factors alone, not CRC risk factors, determined whether FOBT/FIT would be used in‐office or at home. Hispanics had greater odds of being screened in‐office using FOBT/FIT (aOR: 2.04; 95% CI: 1.05‐3.99). Compared with those 50‐59 years old, respondents 70‐75 years old were less likely to be screened in‐office using FOBT/FIT (aOR: 0.44, 95% CI: 0.25‐0.79). Similarly, individuals residing in the Western region of the country had lower odds of in‐office FOBT/FIT (aOR: 0.26; 95% CI: 0.11‐0.58). Conclusion: Amid low overall uptake rates of FOBT/FIT in the United States, in‐physician office testing is high, indicative of a missed opportunity for effective screening and poor adherence of physicians to national guidelines. Sociodemographic factors are determinants of uptake of FOBT/FIT at home or in‐office and should be considered in designing interventions aimed at providers and the general population. Abstract : Amid low overall uptake rates of FOBT/FIT in the United States, in‐physician office testing is high, indicative of a missed opportunity for effective screening and poor adherence of physicians to national guidelines.